EFFECTIVENESS OF ZAKAT-BASED PROGRAMS ON POVERTY ALLEVIATION AND ECONOMIC EMPOWERMENT OF POOR WOMEN: A CASE STUDY OF BANGLADESH - Anis, Fahami Muhammad; Kassim, Salina H. (Bank Indonesia, 2016)
Among the many problems facing Bangladesh, poverty remains a key problem affecting millions of lives. During the past few decades, many initiatives have been implemented such as microcredit and cash transfer programs, yet the results seemed to be ambiguous. New frontiers are now sought to find new sources of finance which could offer a more effective and sustainable solution to the root cause of the poverty problem. Considering the idea of entrepreneurship and group-based development approach of microcredit, a zakat-based development approach was initiated in Bangladesh at a private level by an organization called Center for Zakat Management (CZM) for poverty alleviation and sustainable economic empowerment targeting poor women in rural areas. This paper aims to assess the effectiveness of the CZM efforts in utilizing zakat funds for promoting entrepreneurship among poor rural women. Focusing on the case of Bangladesh, this study assesses the effectiveness of zakat on aspects such as income, house hold expense and fixed asset accumulation of the poor client based on the “before and after” approach. Groups comprising of poor individuals and families are given equity capital/seed money and are encouraged to embark on small businesses according to their own liking. The groups are supervised for a period of a minimum of three years to ensure all individuals within the group are able to continue with their activities and ultimately, free themselves from the shackles of poverty and graduate into sustainable livelihood. Results indicate a significant nominal and real increase in average monthly income, increase in fixed assets and an increase in monthly average household expenditure before and after receiving zakat money. Results also demonstrate factors such as age of the entrepreneur, family size, type of business involved and the amount of zakat received to have a strong influence in determining the success of women entrepreneurs. Education level of the entrepreneur, on the other hand, does not seem to have significant impact on the success or failure of the entrepreneur. The findings from this paper shed light on the effectiveness of zakat-based approach in alleviating poverty and ensuring sustainable economic empowerment of the poor rural women.